Solution Behavior of Bovine Skin Gelatin in the Presence of Cationic Gemini Surfactants. Issue 3 (19th January 2023) - Ansari, Farah; Lal, Hira; Osama, Mohammad; Akram, Mohd.; Kabir‐ud‐Din,
Abstract: The biophysical interaction between gelatin and cationic biodegradable Cm −E2O−Cm gemini surfactants (Cm represents alkyl chain where m=12, 14 and 16; E2 and O denote two ester groups and ethylene oxide, respectively) was analyzed utilizing a multi‐technique approach. The electronic absorption spectroscopy, far‐UV CD and pyrene micropolarity data evinced the formation of a complex between the concerned geminis and the biopolymer. Interestingly, the intrinsic fluorescence spectra do not exhibit concentration dependent behavior with respect to the surfactants giving an impression of poor interaction of gelatin with the geminis. Thereafter, the bulk solution properties, viz. foaming stabilities, viscosities and emulsion stabilities were measured to analyze the effect of binding. All the results combined together led to the inference of significant interaction between gelatin and the gemini surfactants which influence their physicochemical properties. Abstract : The Cm −E2O−Cm gemini surfactants form complexes with bovine skin gelatin at a pH of 7.4. The spectroscopic techniques have evinced the binding between gelatin and the surfactants. Zeta potential values reveal predominantly hydrophobic interactions between the anionic gelatin and cationic geminis. The specific viscosities, foaming and emulsifying properties of the mixtures containing gelatin and geminis are affected due to their binding.